2019
DOI: 10.1074/mcp.ra118.001208
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Plasma Protein Biomarkers for Cervical Cancer Using the Multiplex Proximity Extension Assay

Abstract: Highlights• HPV is being introduced as the primary test in cervical cancer screening programs.• New biomarkers are needed for co-testing of women HPV positive in screening.• Analysis of plasma from women with invasive cervical cancer identified a 11-marker panel.• This signature shows high sensitivity and specificity to identify women with cancer.Human papillomavirus (HPV) is recommended as the primary test in cervical cancer screening, with co-testing by cytology for HPV-positive women to identify cervical le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…It was previously reported that SIRT2 plays a substantial role in cardiovascular disease. In addition, SIRT2 has been detected in the circulation 11 , however, there is no evidence about the role of circulating SIRT2 in AMI. In the present study, we noted that circulating SIRT2 is an acceptable biomarker for AMI, and the higher plasma SIRT2 level was associated with poorer AMI prognosis, especially for worse cardiac function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously reported that SIRT2 plays a substantial role in cardiovascular disease. In addition, SIRT2 has been detected in the circulation 11 , however, there is no evidence about the role of circulating SIRT2 in AMI. In the present study, we noted that circulating SIRT2 is an acceptable biomarker for AMI, and the higher plasma SIRT2 level was associated with poorer AMI prognosis, especially for worse cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, SIRT2 is expressed in various metabolically relevant tissues (e.g., the heart, brain, and adipose tissue) 10 , and is also detected in circulation 11 . SIRT2 plays a pivotal role in various physiological processes in maintaining metabolic homeostasis, including in ammation, oxidative stress and mitochondrial function, as well as adipocyte differentiation, fatty acid oxidation, gluconeogenesis, and insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many important advances in the prevention of cervical cancer, including HPV vaccines and other treatment methods, promising novel biomarkers for the diagnosis, prognosis, and prediction of cervical cancer remain rather poor [21] . Peroxiredoxins (PRDXs) are a peroxidase superfamily of antioxidant enzymes that catalyze peroxide reduction, consisting of six subtypes in mammalian systems, namely, PRDX1-6.…”
Section: Discussionmentioning
confidence: 99%
“…PEA has been successfully used to detect plasma biomarkers for cancer and cardiovascular diseases. [26][27][28] According to both manufacturers, more than 80% of the assays are expected to detect proteins on ethylenediaminetetraacetic acid-treated plasma from healthy donors. In our study, using the PEA platform, 79.7% of the assays were able to detect proteins in at least 25% of the vitreous samples, whereas only 41.5% of the ECL assays detected proteins in more than 25% of the vitreous samples.…”
Section: Discussionmentioning
confidence: 99%
“…PEA has been successfully used to detect plasma biomarkers for cancer and cardiovascular diseases. 26 28 …”
Section: Discussionmentioning
confidence: 99%